The Influence of the Guided Inquiry Learning Model on the Learning Outcomes of Students at SMPN 2 Kupang (JBIOEDRA: Jurnal Pendidikan Biologi, 2025)
The problem in this study is the low learning outcomes of students in science learning, which is still dominated by teacher-centered methods. This research aims to determine the effect of applying the guided inquiry learning model on the learning outcomes of eighth-grade students at SMPN 2 Kupang on the topic of the human excretory system. The study employed a quasi-experimental method with a Nonequivalent Control Group Design. The sample consisted of class VIII D (experimental, n=32) using the guided inquiry model and class VIII E (control, n=32) using direct instruction. Learning outcomes data were collected through pretest and posttest, and analyzed using descriptive statistics, normality test, homogeneity test, and ANCOVA. The results showed that the average N-Gain of the experimental class was 0.63 (high category) and the control class was 0.50 (medium category). The ANCOVA test obtained a significance value of 0.002 < 0.05, indicating a significant effect of the guided inquiry model on learning outcomes. The study concludes that guided inquiry learning can significantly improve student learning outcomes in the human excretory system topic.
Keywords: Guided inquiry, learning outcomes, excretory system, science learning.